Modulating specific antigen presenting cells to harness skin resident T cells during Staphylococcus aureus vaccination - Smith, Megan (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Staphylococcus aureus is one of the leading causes of skin and soft tissue infections worldwide. Its virulence and the rise in antibiotic resistant strains highlights the urgent need for alternative therapies to standard antibiotics. Although numerous efforts have been made to develop a vaccine, none have proven successful in clinical trials. It has been hypothesised that due to immune imprinting that occurs due to a life-long exposure to this organism either through colonisation or sub-clinical infection, that there is a bias toward a regulatory response that is recalled during re-infection and vaccination. Therefore, strategies are needed to overcome the effects of this pre-exposure. Previous work has highlighted the importance of CD4+ memory T cells that reside within the skin, and upon infection with S. aureus produce both IL-17A and IFN-y, which recruit neutrophils to the site of infection leading to a reduction in bacterial burden. Harnessing these cells through a vaccination strategy would logically represent a strategy for effective vaccines. However, immunosuppressive programs that are activated due to prior exposure need to also be overcome to ensure a functional T cell response is induced. The aim of this thesis was to identify a specific population of antigen presenting cells that are directly involved in the priming of T cells in both mice and humans and to investigate the potential to modulate their interactions to boost a protective pro-inflammatory response over an immunosuppressive. Using a mouse model of subcutaneous S. aureus infection, single-cell RNA sequencing was applied to map the immune landscape of antigen presenting cells at various timepoints across a primary and secondary infection. A population of mature regulatory DCs (mregDCs) were identified which had the potential to interact with CD4+ T cells, Tregs, and gd T cells. By modulating the interactions between mregDCs and Tregs through the blockade of an immunosuppressive ligand (CD200), a more protective response was achieved, leading to the reduction of bacterial burden, lesion size, and an increase in the % of IL-17A+ CD4+ T cells upon a secondary infection with S. aureus. Within the human skin a similar population of mregDCs were found as a resident DC population. Blocking the interaction of CD200/CD200R1 in vitro led to an increased production of IL-17A and IFN-y upon exposure to S. aureus, confirming that certain immunoregulatory interactions can be modified within the human response to promote a more pro-inflammatory protective response. Overall, this project provides key mechanistic insights into how regulatory DCs shape T-cell responses to S. aureus and demonstrates that targeted disruption of pathways such as the CD200/CD200R1 can enhance protective IL-17A/IFN-y immunity. These findings offer a foundation for future vaccine and immunotherapeutic strategies to overcome S. aureus induced tolerance.
APPROVED
Keywords: Immunology; Dendritic Cells; Staphylococcus aureus; Immune Checkpoint Blockade; CD4 T cells; Vaccination